The evil men do [large type] : a Ralph Compton novel - Compton, Ralph; Robbins, David, 1950- (Wheeler Publishing, 2015)
"If things are quiet in the little town of Sweetwater, Marshal Fred Hitch sees no reason to make waves. But when Tyree Johnson shows up, Fred's relaxed nature is put to the test. At fifteen years old, Tyree is a tough-as-nails bounty hunter with no patience for anyone calling him "boy." He's come to apprehend a killer who escaped from Cheyenne and has been hiding in plain sight in Sweetwater. To save face and his town's good name, Fred must ride with Tyree and his prisoner all the way to Cheyenne. The unlikely pair has a rough trail ahead of them, and as tough as Tyree is, he has some lessons to learn about the evil men do--and how to survive it."